Assessment of abdominal aortic diameter by computed tomography - Singh, Sushma; Sharma, Bhoj Raj; Thapa, Madan; Khatri, Namrata; Sunar, Elisha; Kafle, Sushmit (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: The aim of this study was to assess the diameters of abdominal aorta of normal Nepalese people by using computed tomography (CT) scans of Abdomen and to correlate the diameters with the patient’s age and gender. CT measurements of abdominal aorta are useful in age estimation and in clinical procedures. Methods: This retrospective study was performed in the Department of Radiology and Imaging, Gandaki Medical College, Nepal during the period of four months from December 2023 to April 2024. Data of total 100 patients are collected who underwent CT abdomen or CT Intra Venous Urography (IVU) of which 49 were males and 51 were females. Age and gender were noted, diameters of abdominal aorta were measured at the suprarenal and infrarenal level i.e. at T12 and L3 vertebral levels in Cannon Prime SP Aquilion with 160 slice CT scanner system. Results: The mean diameters of the suprarenal and infrarenal abdominal aortas measured at T12 and L3 vertebral levels were 18.98±3.45 mm and 15.19±2.46 mm in men and 18.53±2.79 mm and 14.34±1.92 mm in women respectively. The ratio of the infrarenal to suprarenal abdominal aortic diameters was 0.80±0.06 in men and was 0.77±0.06 in women. Conclusions: This study concluded that the diameter of abdominal aorta increased with increase in age and vice versa. Also, there was no significant difference in suprarenal and infrarenal abdominal aortic diameter between male and female.